Web Marketing FOR DUMmIES - Jan Zimmerman (Wiley Publishing, Inc., 2007)
Doing something the same way over and over again can be boring, but consistency makes stuff easier to understand. In this book, those consistent elements are conventions. There are only a few: When URLs (Web addresses) appear within a paragraph, caption, or table, they look like this: www.dummies.com. New terms appear in italics the first time they’re used, courtesy of the copy editor. Anything you have to type is in bold, but frankly, I don’t think you have to type a single thing in this book. Mostly, you just have to think. Fortunately, Web marketing is platform- and operating-system-independent. It doesn’t matter whether you’re on a Mac with OS X or a PC running Windows XP, but I do recommend a high-speed Internet connection. You can no longer realistically monitor your Web site, upload content, review statistics, or research your market at turtle speed (dialup).